The FEMMES.UP corpus: a pragmatic analysis of humorous styles in female stand-up comedy - Linares Bernabéu, Esther (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The present study is based on the classification of styles proposed in the Humor Styles Questionnaire (Martin, et al. 2003). Taking a corpus of stand-up comedy performances, the analysis of the markers used in these examples of humorous discourse aims to reveal which humorous styles are adopted by comedians in performances, and what relationships these comedians have with their own speech styles and communicative intentions. The FEMMES-UP corpus comprises 15 humorous monologues performed by 15 Spanish female comedians. Each performance has been transcribed and divided into humorous sequences, a humorous sequence understood as a series of interventions on a given topic that are interrupted by laughter, applause, and even comments from the audience. In this way, FEMMES-UP yields 504 sequences, amounting to 805 minutes of comedy and 97,749 words. The findings show how female comedians make use of a variety of different humour markers, and distinctive comedic styles, as discursive tactics to represent their intentions as speakers.